Школьная королева - Мид-Смит Элизабет Томасина (Маленькие женщины, 2016)
Экземпляры: ф.18 (20180528) / Инвентарный номер: 2945 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: М 57 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44